A comparison of men and women referred to provincial correctional mental health services in Ontario, Canada. (9th October 2022) - Ray, Ipsita; Fulham, Lindsay; Simpson, Alexander I.; Vogel, Tobias; Gerritsen, Cory; Patel, Kiran; Jones, Roland M.
Abstract: Background: Women comprise around 15% of admissions to provincial correctional institutions in Canada. Women in custody are known to have a high prevalence of mental health concerns, but little is known about how those referred to mental health services compare with referred men at a similar stage of imprisonment. Aims: Our aim was to describe and compare clinical, social and demographic characteristics of a complete cohort of custodially remanded men and women who were referred to mental health services while under custodial remand in two correctional institutions. Methods: We carried out retrospective analysis of data obtained from 4040 men and 1734 provincially detained women referred to mental health services in two correctional centres holding mainly pre‐trial prisoners and serving a large mixed urban‐rural catchment area in Toronto, Canada over a nearly five‐year period. Men and women were first screened using the Brief Jail Mental Health Screen. Those who screened positive were assessed using the Jail Screening Assessment Tool the Brief Psychopathology Rating Scale—Expanded (BPRS‐E) and the Clinical Global Impression—Corrections (CGI‐C). Results: There were many similarities between men and women, but also some important differences. Women were more socioeconomically disadvantaged than men. More women than men reported having children, yet fewer reported having any form of employment or social supports, although men were more likely to report unstable housing. In addition, women were significantly more likely to have mood and anxiety problems and to be self‐harming, but did not differ from men in current psychotic symptoms. We also found differences in patterns of substance use, with a higher proportion of women using heroin and methamphetamines but fewer women having accessed addiction services. Conclusions: Our findings have implications for clinicians and service planners. They underscore the value of systematic screening for identifying need. More specifically, they suggest need for increased availability of addiction services for women as well as ensuring support for those women who have dependent‐age children. Improvement in supports for entry into employment is particularly needed for women, while men are particularly likely to need access to stable housing.